Temperature effect on optical properties of nickel (ii) phthalocyanine tetrasulfonic acid tetrasodium salt (NiPcTs) organic thin films - Abdulameer, Ameer F. (Iraqi Journal of Physics, 2019)
This study describe the effect of temperature on the optical properties of nickel(ii) phthalocyanine tetrasulfonic acid tetrasodium salt (NiPcTs) organic thin films which are prepared by spin coating on indium tin oxide (ITO-glass). The optical absorption spectra of these thin films are measured. Present studies reveal that the optical band gap energies of NiPcTs thin films are dependent on the annealing temperatures. The optical band gap decreases with increase in annealing temperature, then increased when the temperature rising to 473K. To enhance the results of Uv-Vis measurements and get more accurate values of optical energy gaps; the Photoluminescence spectra of as-deposited and annealed NiPcTs thin films was studied. FTIR measurements for NiPcTs thin films also carried out in this work and gave good information about the NiPcTs bonds and its locations as a compared with H2Pc as a reference.